2006
DOI: 10.1115/1.2188952
|View full text |Cite
|
Sign up to set email alerts
|

Micron and Submicron-Scale Characterization of Interfaces in Thermal Interface Material Systems

Abstract: One of the key challenges in the thermal management of electronic packages are interfaces, such as those between the chip and heat spreader and the interface between a heat spreader and heat sink or cold plate. Typically, thermal interfaces are filled with materials such as thermal adhesives and greases. Interface materials reduce the contact resistance between the mating heat generating and heat sinking units by filling voids and grooves created by the nonsmooth surface topography of the mating surfaces, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Therefore, it is likely that the thermally conductive fillers are not functioning in the region due to the presence of the filler depletion layer. Such filler-depletion layer (FDL) has been observed for a curing TIM 14,15 but the current result suggests that it can also occur for non-curing TIM even without phase transition. Figure 3(a)-3(c) also shows that the TDTR signal obtained for pure Silicone oil agrees well with the heat conduction model with the bulk thermal conductivity of Silicone (0.15 Wm…”
Section: -4 Yada Et Almentioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, it is likely that the thermally conductive fillers are not functioning in the region due to the presence of the filler depletion layer. Such filler-depletion layer (FDL) has been observed for a curing TIM 14,15 but the current result suggests that it can also occur for non-curing TIM even without phase transition. Figure 3(a)-3(c) also shows that the TDTR signal obtained for pure Silicone oil agrees well with the heat conduction model with the bulk thermal conductivity of Silicone (0.15 Wm…”
Section: -4 Yada Et Almentioning
confidence: 63%
“…subtracting the separately measured thermal resistance of suspended TIM), they have found that ITR can be significant and the values range from 2 mm 2 KW −1 to 20 mm 2 KW −1 . Furthermore, Gowda et al 15 observed the interface between the cured TIM and Al by computed tomography, acoustic microscopy, and scanning electron microscopy, and showed the existence of delamination and filler-depleted/resin-rich region at the interface.…”
mentioning
confidence: 99%
“…Many techniques, such as C-Mode Scanning Acoustic Microscopy (CSAM) [5,6], radiography [7], infrared microscopy [7], scanning electron microscopy [8], and transient thermal tomography [9], have been employed in an effort to characterize the physical integrity of TIM bond layers while under stress, or after being stressed.…”
Section: Introductionmentioning
confidence: 99%
“…Various nonintrusive means have been used to characterize the quality of TIM layers, such as acoustic microscopy [2,3] and Xray methods [3]. An infrared microscopy technique to characterize a TIM layer through a silicon wafer was demonstrated by Hu et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Thermography techniques [5,6] may be used to characterize the transient thermal response of an interface, and thus infer the existence and location of voids. High-resolution methods, such as scanning electron microscopy [3], have also been applied to TIM layers. Although the above techniques provide microscale or nanoscale resolution, the necessary equipment, sample preparation, and expertise required for these methods may be prohibitive in many industrial applications.…”
Section: Introductionmentioning
confidence: 99%